OPTIMASI PROYEK PEMBANGUNAN GEDUNG WORKSHOP TEKNIK MESIN UPN VETERAN JAWA TIMUR DENGAN METODE TIME COST TRADE OFF - Muhammad Rafli Nurabidin; Michella Beatrix (Racic : Rab Construction Research, 2024)
Projects are temporary initiatives with limited time, resources, and goals. Due to time and financial constraints, project planning is crucial, with project management being a key factor in its success. Consistency in the quality, cost, and time of a construction project requires the selection of effective construction methods. The purpose of this study is find out the construction costs by adding working hours using the TCTO method, knowing the acceleration of construction time by adding working hours using the TCTO method. These methods impact the construction duration, material usage, equipment, and labor. In the case of the Workshop Building for Mechanical Engineering at UPN Veteran East Java, issues arose during boredpile work due to marshy soil, limiting the installation to only 2 points per day, resulting in a 9-week delay from week 11 to week 20. Additionally, challenges included the time-consuming disposal of boredpile soil and equipment damage, requiring weekly repairs lasting approximately 4 hours. Therefore, acceleration is needed to address these delays, which can be achieved through the Project Crashing approach using the Time Cost Trade Off (TCTO) method.